Under the magician's spell - Stine, R. L. (New York : Scholastic, 1996)
You are invited to choose one of 20 spooky endings as your little sister takes a book of magic spells and the magician uses every terrifying magic trick to get it back
"An Apple paperback"
4
8-12
430
Keywords: Magic -- Fiction; Horror stories; Plot-your-own stories